Meeting Report of the Fifth International Cancer Epigenetics Conference in Beijing, China, October 2016. (July 2017) - Gao, Dan; Herman, James G; Cui, Hengmi; Jen, Jin; Fuks, Francois; Brock, Malcolm V; Ushijima, Toshikazu; Croce, Carlo; Akiyama, Yoshimitsu; Guo, Mingzhou
Fifth International Cancer Epigenetics Conference, Beijing, China, 21–23 October 2016 This meeting reported many new findings in the field of cancer epigenetics, including basic science, translational and clinical studies. In this report, we summarize some of the main advancements and prospects in cancer epigenetics presented at this meeting.